University Students’ Perceptions and Attitudes Toward AI Use in Learning: Benefits and Concerns - Halim Halim; Najma Nur Mawaddah; Yulian Widya Saputra; Sutriani Sutriani (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
Artificial Intelligence (AI) has been increasingly utilized in higher education and has influenced the way students learn and complete academic tasks. This study aims to examine university students’ perceptions and attitudes toward the use of Artificial Intelligence in the learning process. A descriptive quantitative approach was employed, involving 74 active students from the Geography Education study program. Data collection was conducted via an online questionnaire using a five-point Likert scale, and the data were analyzed using descriptive statistics and score interpretation techniques. Research findings suggest that students' perspectives on the use of Artificial Intelligence fall into the positive category, with 73.5% reporting a positive view. At the same time, students' attitudes toward AI use also fall into a positive category, reaching 74.1%. These findings suggest that Artificial Intelligence is perceived as beneficial in enhancing learning efficiency, motivation, and student Engagement. However, the study also reveals students' concerns regarding potential over-reliance on AI, which may reduce critical thinking skills, as well as issues related to data privacy and security. Based on these findings, this study recommends that universities provide training on Artificial Intelligence (AI) ethics, establish privacy protection guidelines, and implement academic integrity policies.